Imaging in pregnancy-associated breast cancer: a case report - Untanas, Audrius; Grigaitė, Indrė; Briedienė, Rūta (Acta medica Lituanica, 2019)
Background. PABC (pregnancy-associated breast cancer) is a rare condition that appears as a malignancy in 1 per 3000 pregnant women and is one of the most common cancers diagnosed during pregnancy or the postpartum period. If a woman who is pregnant or within a year after delivery has complaints of a palpable breast mass, it could undeniably be a malignant mass of the breast. That is why an ultrasound should be performed for all pregnant or lactating women who detect a palpable breast mass that persists for two or more weeks. Case report. Our case report presents a pregnant 40-year-old previously healthy female at 36 weeks gestational age with a complaint of a palpable left breast mass for two months period. The initial ultrasound showed a breast tumour of irregular shape, solid and hypervascular mass. Conclusions. Early diagnostics of PABC is of crucial importance in order to offer the best possible outcomes for the patient and foetus.
Keywords: PABC; breast cancer; pregnancy; ultrasound; magnetic resonance